MONITORING OF MANGROVE ECOTOURISM AREA USING NDVI, NDWI, AND CMRI IN DODOLA ISLAND, MOROTAI ISLAND REGENCY, INDONESIA (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2022)
The development of tourism infrastructure causes land-use change or land conversion from green open spaces into tourism economic areas. The utilization of mangrove areas as an ecotourism attraction needs to be monitored regularly so that facilities and infrastructure development do not threaten the sustainability of mangrove vegetation. This article aims to identify the distribution of mangroves using the Normalized Difference Vegetation Index (NDVI), Normalized Difference Water Index (NDWI), Combined Mangrove Recognize Index (CMRI) model in Morotai Island Regency, North Maluku Province, Indonesia. The perspective of sustainable ecotourism is used to discuss the socio-cultural context of the Morotai community, especially the people of Kolorai Island. This study adopted a mixed-method. Data processing is divided into two stages: the first stage, mapping the distribution of mangroves on Dodola Island using Landsat 8 Operational Land Imager (OLI) satellite imagery from 2013-2021 based on NDVI, NDWI, and CMRI calculations; the second stage, triangulation. The results of this study indicate that in 2017, there was a decrease in the value of NDVI and CMRI in Zone 1, Zone 2, and Zone 3 as a mangrove ecotourism area on Dodola Island. It indicates a threat to the mangrove ecosystem if infrastructure development causes a decrease in the value of the vegetation index significantly significant from year to year. Thus, it is necessary to control infrastructure development programs by involving local communities in the maintenance of mangrove ecosystems.